FENOMENA KOMUNIKASI KOMUNITAS KELAS INSPIRASI (STUDI FENOMENOLOGI SOCIAL MOVEMENT PADA ANGGOTA KOMUNITAS KELAS INSPIRASI PEKANBARU) - Bosma, Feby Diani; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research focuses on social and educational issues has always been the subject of debate that became a phenomenon in Indonesia. Social movement become an alternative to change the people it self. Social movement in Pekanbarucan be interesting research. Kelas Inspirasi community as a social movement in Pekanbaru be a forum for the members to inspire the next generation to improve the quality of human resources. This research intend to find out how the motives of members, how they interpret the social movement, and communication experience in running social movement in pekanbaru.This research uses qualitative method with phenomenology approach. The subjects consist of ten volunteer informants and community committee of Kelas Inspirasi, selected by using purposive technique. The data for this research collected through by interview, observation and documentation. To test the validity of the data used the method of extension of participation and triangulation.The result of this research is to find out motives of Kelas Inspirasi members, an the result is consist of because motives include, human factors, trial, passion in education. And in order to motives, adding friends and relationships, helping others, introducing the profession and providing insight into the future purpose, adding experiences and developing ideas. Members of Kelas Inspirasi Community mean social movement as ways to be happy, ways to share, and positive activities.The communication experience by members of Kelas Inspirasi Pekanbaru community consists of pleasant communication experience in the welcome speeches of principals and teachers, the enthusiasm of children, adding friendships and relationships and adding new experiences. Second, unpleasant communication experiences include access to location difficulties, rejection from several schools, and licensing issues.Key Word: Social Movement, Community, Kelas Inspirasi Pekanbaru